Acoustic radiation calculations by a hybrid separation of variables - boundary element method - Brański, A. (Archives of Acoustics, 2001)
A new hybrid method (HM) solution to the radiation problem is presented. The HM is based on the separation of variables method and the boundary element method. An idea of the HM consists in the modelling of acoustic variables only by the boundary element method using their discrete values. The geometry of the problem is described exactly. The HM enables to solve boundary acoustic problem in an orthogonal curvilinear system of coordinates. In the paper the method is applied to acoustic radiation by axially vibrating cup or ring set on the sphere. The hybrid radiation solution is compared to the well known analytical one.